3D printed concrete with recycled sand: Pore structures and triaxial compression properties. (May 2023) - Wu, Yiwen; Liu, Chao; Bai, Guoliang; Liu, Huawei; Meng, Yisheng; Wang, Zhihui
Abstract: The mechanical properties and failure criteria of 3D printed concrete under triaxial compression are the basis of calculations for structural design. Incorporating recycled sand into 3D printed concrete can promote early structural formation and has significant environmental benefits. In this study, the pore structures of 3D printed recycled mortar (3DPRM) were characterized by MIP and X-CT tests. The triaxial mechanical properties in the Z-direction were measured at confining pressures of 0, 5, 10, and 15 MPa. The results showed that the incorporation of recycled sand increased the porosity and pore diameter of 3DPRM specimens in various diameter ranges but did not significantly change the sphericity and orientation of the pores. The crack development direction of 3DPRM specimens under triaxial compression depended on both the principal stress direction and the pore structure. The confining pressure increased the strength and compressive toughness of the 3DPRM specimens, and the sensitivity of the 3DPRM specimens to the confining pressure increased with increasing replacement rate. By analyzing the influence mechanism of recycled sand incorporation on 3DPRM strength, a dual deterioration hypothesis based on the pore structure and interface transition zone of 3DPRM was proposed, and the corresponding strength model was established.